(untitled) (Fiep Bulletin - online, 2013)
Volleyball sitting, according to CPB (2011) in 1956 in the Netherlands with the junction of sitzball, German sport played sitting and without network and voleiboll, after the founding of the first Club for the disabled in 1953. Since then the sitting volleyball has been considered one of the most important team sports for athletes with disabilities. Noce, Simim and Mello (2009) say that regular practice of physical activity by disabled people, gets great positive effects to the physical, mental and social health, i.e., better quality of life. The study aimed to describe and analyze body composition and neuromotores aspects of sitting volleyball athletes in Rio de Janeiro. The subjects were seated volleyball practitioners, volunteers with ages 34.50 ± 13.05 years, male. On the IPAQ, 40% athletes qualified very active, 50% active and 10% not active. The test manual grasping the result was 34.60 + 10.96 kgf for right upper limb, classifying the group as weak and 33.89 ± 11.16 kgf to the left upper limb, classifying them as weak. The Group analyzed had a fat percentage of 14.67 ± 3.30, being considered as good, adverse to that found by Horta et al (2009) with practitioners of sports adapted, classified as average. In view of the lack of studies that make this characterization of the neuroantropométrico profile of the athletes of volleyball sitting, this so didn’t have to compare with other teams, and the comparison made with different groups have already studied. Such studies would provide development of sport training of sport adapted, seeking prestige and acceptance through its national and international results, which would help in the search for truth and standardization of specific techniques for physical assessment of athletes with disabilities.